Polycystic ovarian syndrome and insulin resistance: a South Indian study - Anuradha, V.; Gangadharan, Keshav; Saxena, Rajiv Kumar; Krishna, L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age. Some studies have characterized different aspects of women presenting with PCOS. In this study we characterise the association of insulin resistance (IR) in patients with PCOS in the southern Indian state of Andhra Pradesh. Methods: A total of 50 women diagnosed to have PCOS according to Rotterdam criteria were studied. IR was estimated using Homeostatic model assessment - insulin resistance (HOMA-IR) and clinical characteristics were recorded. Results: The prevalence of IR among the study population was 36%. All PCOS patients with IR were overweight or obese, and had impaired glycaemic status, 75% of PCOS patients with IR also had features of hirsutism. Conclusions: Considering the prevalence of IR, obesity and impaired fasting glucose in women with PCOS, early institution of treatment by lifestyle changes or medication would lead to improvement in reproductive and metabolic abnormalities.